2007
DOI: 10.3892/ijo.30.1.129
|View full text |Cite
|
Sign up to set email alerts
|

The gene expression profile represents the molecular nature of liver metastasis in colorectal cancer

Abstract: Abstract. The major cause of death in colorectal cancer is related to liver metastasis. Although the metastatic process has been well studied, many aspects of the molecular genetic basis of metastasis remain unclear. Elucidation of the molecular nature of liver metastasis is urgent to improve the outcome of colorectal cancer. We analyzed the chronological gene expression profiles of 104 colorectal samples corresponding to oncogenic development including normal mucosa, localized and metastasized primary tumors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…Therefore, the microarray or next generation sequencing transcriptome technologies have proven as a valuable source of candidate metastasis-associated genes (6)(7)(8)(9). We recently used the oligonucleotide microarrays to perform high-throughput screening of global gene expression in a chicken metastatic cell line derived from v-src-induced sarcoma and its nonmetastatic subclone (10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the microarray or next generation sequencing transcriptome technologies have proven as a valuable source of candidate metastasis-associated genes (6)(7)(8)(9). We recently used the oligonucleotide microarrays to perform high-throughput screening of global gene expression in a chicken metastatic cell line derived from v-src-induced sarcoma and its nonmetastatic subclone (10).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of colorectal cancer (CRC) has increased significantly in recent years, in concert with the changing lifestyle (Kohno et al, 2007). The major cause of death in CRC is liver metastases (Yamasaki et al, 2007). Although treatment of CRC has improved recently, it fails in approximately one-third of the patients who need an alternative strategy for coping with death (Jones et al, 2007).…”
mentioning
confidence: 99%
“…A number of studies have reported the possible benefits of cluster analysis in studies investigating gene variation in colorectal cancer (29)(30)(31)(32). The present study performed data mining employing cluster analysis and observed a tendency toward differences in the incidences of synchronous and heterochronous liver metastases among groups A-D.…”
Section: Discussionmentioning
confidence: 91%